THE OUTCOME OF PREGNANCY AND CHILDBIRTH IN WOMEN WITH IMPAIRED VAGINAL BIOCENOSIS - Yuldasheva Farangiz Ismatiloevna; Samiyeva Gulnoza Utkurovna; Zakirova Nodira Islamovna (Scholar Express Journals, 2022)
Dysbiotic disorders of vaginal microbiocenosis increase the risk of various complications from the mother and fetus, determine the course of pregnancy and its outcome. In this article, a study of the biocenosis of the vagina of 96 pregnant women from early pregnancy was conducted. It is shown that timely detection of pregnant women with a high risk of infectious and inflammatory complications and their proper management will reduce the frequency of complications in the mother, fetus and newborn
Keywords: Normocenosis; dysbiosis; microflora; trimester